Effect of Soy Isoflavones Compared to Estradiol Valerate in Menopausal Women assessed by Menopause Quality of Life Questionnaire - Almon, Willy Kurnia; Siregar, Muhammad Fidel Ganis; Tala, M. Rhiza Z.; Sitepu, Makmur; Adenin, Ichwanul; Lubis, Muara Panusunan (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: There has recently been a global effort to develop preparations that aim for benefits of hormone replacement therapy with minimal discomfort or risk while isoflavones administration found to relieve complaints related to menopause and has been widely carried out. AIM: The aim of the study is to determine the effect of soy isoflavone compared to estradiol valerate administration in postmenopausal women assessed by the Menopause Quality of Life (MENQOL) questionnaire. METHODS: This is an experimental study with pre-post test non-randomized design using data from postmenopausal women who were divided into two groups, namely, group I Estradiol Valerate group which is 16 menopausal women were given Estradiol Valerate and group II Soy Isoflavone Supplements group which is 16 menopausal women were given Soy Isoflavone Supplements. RESULTS: It was found that in estradiol valerate group, total MENQOL value before estradiol valerate administration was 81.56 ± 19.77, and after administration was 74.55 ± 16.82 with p = 0.002, which indicates there is a significant total MENQOL score difference before and after administration estradiol valerate. In the soy isoflavone group, the total MENQOL scores before soy isoflavone administration were 91.0 ± 16.31, and after administration was 83.08 ± 13.85 with p = 0.001, which indicated that there was a significant total MENQOL score difference between before and after administration soy isoflavone. CONCLUSION: In comparison of menopausal complaints based on MENQOL scale in Estradiol Valerate and Soy Isoflavone groups after intervention, it was shown that there were significant differences in total MENQOL value after intervention.